Financial Literacy, Self-Efficacy, and Financial Behaviour of College Students - Anastasia Anggarkusuma Arofah (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2019)
Many policies have been provided to improve the financial literacy of individuals, especially those involving financial education programmes. However, positive financial behaviour requires more than financial literacy: an individual must also have self-confidence or self-belief in their ability to manage their personal finances. This attribute is known in the psychological literature as “self-efficacy”. This paper examines the importance of financial literacy and self-efficacy in affecting individual financial behaviour. The research is conducted through a survey of 129 undergraduates of Economics Education, at Sebelas Maret University. The results of the research show that both financial literacy and self-efficacy have positive and significant effects on financial behaviour. Undergraduates with high financial literacy are more likely to hold investment and savings products and are less likely to hold debt-related products. Similarly, undergraduates who have high self-efficacy are likely to be better at managing their personal finances. Moreover, the significance of financial literacy and self-efficacy has important implications for the development of policies that aim to improve financial behaviour among college students through financial education programmes.